2017
DOI: 10.1002/jor.23498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of joint immobilization on changes in myofibroblasts and collagen in the rat knee contracture model

Abstract: The purpose of this study was to examine the time-dependent changes in the development of joint capsule fibrosis and in the number of myofibroblasts in the joint capsule after immobilization, using a rat knee contracture model. Both knee joints were fixed in full flexion for 1, 2, and 4 weeks (immobilization group). Untreated rats were bred for each immobilization period (control group). Histological analysis was performed to evaluate changes in the amount and density of collagen in the joint capsule. The chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 52 publications
5
45
0
2
Order By: Relevance
“…capsule, and synovial membrane, while the myogenic components are lesions of the muscle, tendon, and fascia. 6,12 Arthrogenic components, particularly regarding the joint capsule, are reportedly important factors in the formation of immobilization-induced joint contracture. 6,13,14 Reported changes in the capsule after immobilization include proliferation of connective tissues within the joint space, and adhesions in the capsule and synovial membrane.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…capsule, and synovial membrane, while the myogenic components are lesions of the muscle, tendon, and fascia. 6,12 Arthrogenic components, particularly regarding the joint capsule, are reportedly important factors in the formation of immobilization-induced joint contracture. 6,13,14 Reported changes in the capsule after immobilization include proliferation of connective tissues within the joint space, and adhesions in the capsule and synovial membrane.…”
mentioning
confidence: 99%
“…6,12 Arthrogenic components, particularly regarding the joint capsule, are reportedly important factors in the formation of immobilization-induced joint contracture. 6,13,14 Reported changes in the capsule after immobilization include proliferation of connective tissues within the joint space, and adhesions in the capsule and synovial membrane. 15,16 Some studies reported that joint capsule fibrosis may occur in the posttraumatic joint contracture caused by joint immobilization in flexion in rabbit or rat models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis in the joint components is believed to be the major factor contributing to development of arthrogenic contracture in injured (Fukui et al 2000, Fukui et al 2001, Gao et al 2017, Li et al 2013a and immobilized joints (Sasabe et al 2017). For example, administration of decorin, which suppresses bioactivity of cell adhesion, as well as fibrotic regulators, such as transforming growth factor-beta, can improve restricted joint motion in the rabbit intra-articular adhesion model (Fukui et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to this, there are differences in the rate of progression of joint contracture caused by immobilization between different species. 6 , 7 Despite this, joint function can be restored by removing joint immobilization and reactivating. For example, flexing knee joint contracture that occurs in rats in 2 weeks can be completely restored, but it is difficult to restore completely when immobilization time over 4 weeks.…”
Section: Introductionmentioning
confidence: 99%